Tunisia in a changing climate: assessment and actions for increased resilience and development. - Verner, Dorte (World Bank Studies, 2013)
This report assesses climate risks and opportunities and proposes actions. It provides a synthesis of evidence of climate variability and change, impacts, and uncertainties associated with climate change that may affect Tunisia s water, land, agriculture, and coastal zones. The report then provides a detailed analysis of the potential impacts of climate change on food security and gross domestic product (GDP) as well as on local populations looking in particular at seven governorates. The report goes on to discuss possible policy options for reducing human vulnerability and for better adapting to climate variability and change. The report provides guidance to policy makers in Tunisia in three ways. First, it provides a Framework for Action on Climate Change Adaptation, represented by an adaptation pyramid. Second, it puts forward a typology of policy approaches that are relevant to the region in order to facilitate the formulation of effective policy responses by decision makers. Finally, a matrix is provided, which outlines key policy recommendations. Actions align with the World Bank s 2012 Interim Strategy Note (ISN) for Tunisia, which guides the World Bank investments in Tunisia over the next two years and is focused on three main areas of intervention: (1) sustainable growth and job creation, (2) the promotion of social and economic inclusion by improving access to basic services for underserved communities and improving the efficiency of social safety net programs, and (3) strengthening governance through improved access to public information as the basis for increased social accountability and transparency.